2017
DOI: 10.1016/j.anbehav.2017.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Does the removal of finder's share influence the scrounging decisions of herbivores?

Abstract: • It is unclear if herbivores use finder's share when making patch-joining decisions. • We manipulated finder's share and food availability to explore these decisions. • At low food availability, goats avoided the finder's share patch after 30 s. • When food availability was high, goats continued to join the finder's share patch. • Thus, both finder's share and food availability influenced patch-joining decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Notably, producing individuals have immediate access to new, undecimated resources before others arrive (i.e. finder's share) [ 4 , 5 ], while scrounging individuals may be limited on resource intake. However, scrounging individuals perform less dangerous exploratory behaviours, which can provide survival advantages [ 6 ], though this may be negated when food is limited [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, producing individuals have immediate access to new, undecimated resources before others arrive (i.e. finder's share) [ 4 , 5 ], while scrounging individuals may be limited on resource intake. However, scrounging individuals perform less dangerous exploratory behaviours, which can provide survival advantages [ 6 ], though this may be negated when food is limited [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…the amount of food eaten by the patch holder prior to other individuals joining the patch; Vickery et al 1991) had been removed, was lower than what could be obtained by an individual searching for its own patch. For example, Kok et al (2017) found when food availability was low (40 & 100 g), that individuals would avoid patches in which patch holders had fed for as little as 30 seconds. They suggested that this was likely due to the patch holders extensively reducing food availability, and thus patch attractiveness to potential joiners.…”
Section: Discussionmentioning
confidence: 99%